The concerns of beginning teachers in rural contexts - Sánchez Sánchez, Gerardo Ignacio (2019)
The objective of the study was to determine and problematize the worries that the labor insertion of graduates of Primary Pedagogy faces in cultural conditions of rurality. This is important, since the incorporation of the new teachers into the labour field represents difficulties and challenges that must be solved in a limited period, if we intend to advance in the professional development and avoid the abandonment of the Profession. The research is qualitative exploratory - descriptive, based on a non-experimental transectional design with administration of a questionnaire aimed at fifty beginning teachers in various rural labor contexts of the Maule Region, Chile, and deepens the problem with the development of semi-structured interviews to eight teachers in their work contexts. The results show that labor insertion contexts condition (facilitate or limit) the entrance to teaching, and explain the presence of worries of diverse nature linked to available knowledge, associated fears and difficulties of legitimacy that have had to overcome. In conclusion, unveiling these concerns is key to contributing to the accompaniment processes that begin to be designed and implemented in the national context, understanding that their effectiveness goes to focus the support on the recognition of the beginning teacher as an actor and not a simple factor of the system.